Testing market integration : an analysis of fresh sea fish prices in Java - Zulham, Armen (1988)
Two kinds of analyses were undertaken to study fresh sea fish commodity in Indonesia, namely,consumption of fresh sea fish in Indonesia and the pricing efficiency analysis of fresh sea fish in Java. The data for consumption analysis were collected from Biro Pusat Statistik (BPS). A consumption equation was estimated and the adjustment coefficient was found to be 0.6186 suggesting that the adjustment to optimal consumption level was quite rapid. The results also suggest that in the short-run, the elasticities of demand with respect to price of fresh sea fish, income and price of SUbstitute are -0.00035, 0.15379, and 0.00003 respectively ,which were in elastic.